The effects of different types of taxes on soft-drink consumption - Abdulfatah Sheikhbihi Adam; Sinne Smed (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2012)
Monthly data from GfK Consumerscan Scandinavia for the years 2006 – 2009 are used to estimate the effects of different tax scenarios on the consumption of sugar sweetened beverages (SSB's). Most studies fail to consider demand interrelationships between different types of soft-drinks when the effects of taxation are evaluated. To add to the literature in this aspect we estimated a two-step censored dynamic almost ideal demand system where we include the possibilities that consumers have to substitute between diet and regular soft-drinks, between discount and non-discount (normal) brands as well as between different container sizes. Especially the large sizes and discount brands provide considerable value for money to the consumer. Three different type of taxes is considered; a tax based on the content of added sugar in various SSB's, a flat tax on soft-drinks alone and a size differentiated tax on soft-drinks that remove the value for money obtained by purchasing large container sizes. The scenarios are scaled equally in terms of obtained public revenue. Largest effect in terms of reduced intake of calories and sugar are obtained by applying the tax on sugar in all beverages, even though detrimental health effects in terms of increased intake of diet soft-drinks has to be considered. A flat tax on soft-drinks decreases the intake of sugar, but implies a small increase in total calorie intake due to substitution with other SSB's. A tax aimed at removing the value added from purchasing large container sizes increase sugar and total calorie intake due to substitution towards discount brands. Hence the results show the importance of considering substitution between different sizes, brands and discount versus normal brands when simulating the effects of soft-drinks taxation and point toward a tax on the sugar content of SSB's as the most effective in the regulation of obesity.
Keywords: 330; Soft-drinks consumption; taxation; consumer behaviour; two-step censoring